PML2‐mediated thread‐like nuclear bodies mark late senescence in Hutchinson–Gilford progeria syndrome. Issue 6 (29th April 2020) - Wang, Ming; Wang, Lulu; Qian, Minxian; Tang, Xiaolong; Liu, Zuojun; Lai, Yiwei; Ao, Ying; Huang, Yinghua; Meng, Yuan; Shi, Lei; Peng, Linyuan; Cao, Xinyue; et al.
Abstract: Progerin accumulation disrupts nuclear lamina integrity and causes nuclear structure abnormalities, leading to premature aging, that is, Hutchinson–Gilford progeria syndrome (HGPS). The roles of nuclear subcompartments, such as PML nuclear bodies (PML NBs), in HGPS pathogenesis, are unclear. Here, we show that classical dot‐like PML NBs are reorganized into thread‐like structures in HGPS patient fibroblasts and their presence is associated with late stage of senescence. By co‐immunoprecipitation analysis, we show that farnesylated Progerin interacts with human PML2, which accounts for the formation of thread‐like PML NBs. Specifically, human PML2 but not PML1 overexpression in HGPS cells promotes PML thread development and accelerates senescence. Further immunofluorescence microscopy, immuno‐TRAP, and deep sequencing data suggest that these irregular PML NBs might promote senescence by perturbing NB‐associated DNA repair and gene expression in HGPS cells. These data identify irregular structures of PML NBs in senescent HGPS cells and support that the thread‐like PML NBs might be a novel, morphological, and functional biomarker of late senescence. Abstract : Progerin–PML2 mediates the formation of thread‐like PML NBs, which perturb NB‐associated DNA repair and gene expression. The thread‐like PML NBs dictate a "0/1 model" of senescence (0 = no senescence; 1 = complete senescence) and thus label late senescence of HGPS cells. Most other senescence markers fit a "0‒1 model", which requires a threshold value between 0 and 1 to define a senescence stage.